Analisis Kadar Besi (Fe) Pada Tanaman Porang (Amorphophallus Oncophyllus) - Rachmat Saputra (QUANTUM: Jurnal Pembelajaran IPA dan Aplikasinya, 2026)
The nutrient content in porang plants, as with other tuber plants, also contains carbohydrates, fats, proteins, minerals, vitamins and fiber. This study aims to obtain data on the average iron mineral content in Porang Plants. Determination of iron content using the Atomic Absorption Spectrophotometer (AAS) method is based on the atomization of iron compounds in a low pH 2-5. Iron compounds will be atomized with a flame on AAS producing emission rays that produce a wavelength of 248.3 nm for Fe which is captured by the detector which is then digitally converted to produce iron content by comparing it with the appropriate iron standard series in the sample content range, 0.00; 0.20; 0.80; 1.2; and 1.6 mg/L Fe. The analysis results showed that the dry porang tubers contain 32.54 mg/kg of iron, or 0.03254 g of dry flour per 1 kg (32.54 ppm), equivalent to 0.00488 g of iron from dry porang tubers per 1 kg (4.88 ppm), equivalent to 0.00097 g from wet porang tubers per 1 kg (0.97 ppm).